(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This scientific article analyzes the phenomenon of human rights, the history of its occurrence and its place in our public life today. It was emphasized that human rights and freedoms are an important basis for democratic development, civil society and economic reforms. It was disclosed that in recent years, the reforms carried out in Uzbekistan have revealed practical work to protect the rights and legitimate interests of a human.